Measurement of the branching fractions of the decays D+ [right arrow] K−K+K+, D+ [right arrow] π−π+K+ and Ds+ [right arrow] π−K+K+ - Aaij, Roel; Bachmann, Sebastian; Berninghoff, Daniel; Braun, Svende; Comerma-Montells, Albert; D'Argent, Philippe; Dziewiecki, Michal; Gerick, David; Grabowski, Jascha; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; Kecke, Matthieu; et al. (Journal of high energy physics, 2019)
Abstract The branching fractions of the doubly Cabibbo-suppressed decays D + → K − K + K +, D + → π−π+ K + and D s + → π − K + K + are measured using the decays D + → K −π+π+ and D s + → K − K + π + as normalisation channels. The measurements are performed using proton-proton collision data collected with the LHCb detector at a centre-of-mass energy of 8 TeV, corresponding to an integrated luminosity of 2.0 fb−1. The results are ℬ D + → K − K + K + ℬ D + → K − π + π + = 6.541 ± 0.025 ± 0.042 × 10 − 4 , ℬ D + → π − π + K + ℬ D + → K − π + π + = 5.231 ± 0.009 ± 0.023 × 10 − 3 , ℬ D s + → π − K + K + ℬ D s + → K − K + π + , = 2.372 ± 0.024 ± 0.025 × 10 − 3 , $$ \begin{array}{c}\hfill \frac{\mathrm{\mathcal{B}}\left({D}^{+}\to {K}^{-}{K}^{+}{K}^{+}\right)}{\mathrm{\mathcal{B}}\left({D}^{+}\to {K}^{-}{\pi}^{+}{\pi}^{+}\right)} = \left(6.541\pm 0.025\pm 0.042\right)\times {10}^{-4},\hfill \\ {}\hfill \frac{\mathrm{\mathcal{B}}\left({D}^{+}\to\ {\pi}^{-}{\pi}^{+}{K}^{+}\right)}{\mathrm{\mathcal{B}}\left({D}^{+}\to {K}^{-}{\pi}^{+}{\pi}^{+}\right)}=\left(5.231\pm 0.009\pm 0.023\right)\times {10}^{-3},\hfill \\ {}\hfill \frac{\mathrm{\mathcal{B}}\left({D}_s^{+}\to\ {\pi}^{-}{K}^{+}{K}^{+}\right)}{\mathrm{\mathcal{B}}\left({D}_s^{+}\to {K}^{-}{K}^{+}{\pi}^{+}\right), } = \left(2.372\pm 0.024\pm 0.025\right)\times {10}^{-3},\hfill \end{array} $$ where the uncertainties are statistical and systematic, respectively. These are the most precise measurements up to date.
Im Titel sind die Plus- und Minuszeichen hochgestellt, das "s" in Ds+ tiefgestellt
LHCb collaboration: R Aaij, P. d’Argent, S. Bachmann, D. Berninghoff, S. Braun, A. Comerma-Montells, M. Dziewiecki, D. Gerick, J.P. Grabowski, X. Han, S. Hansmann-Menzemer, M. Kecke, M. Kolpin, R. Kopecna, B. Leverington, J. Marks, D.S. Mitzel, S. Neubert, M. Neuner, A. Piucci, N. Skidmore, M. Stahl, S. Stemmle, U. Uwer, A. Zhelezov [und 820 weitere]
Gesehen am 01.08.2019